Evaluation on Energy Efficiency Improvement in Geothermal Power Plant with The Application of Load-based Gas Removal System and Cooling Water Pump Control System - Wibisono Yamin; I.G.B Ngurah Makertihartha; Jenny Rizkiana (Jurnal Rekayasa Proses, 2020)
Efficient Geothermal Power Plant (GPP) operation can be achieved through the optimum use of steam for turbine and auxiliary (ejectors), and minimum possible condenser pressure for maximum energy conversion in the turbine. In all GPPs, a condenser vacuum is maintained by adequate circulation of cooling water and effective operation of ejectors, which absorb the accumulation of Non-Condensable Gas (NCG), mostly CO2 and H2S, and dispose it to the atmosphere. Typically, GPPs are designed for baseload (100% capacity) operation. Therefore, the performance of supporting equipment such as ejectors and cooling water pumps are not sensitive to load-set fluctuations or changes in NCG content. This fact consequently results in constant parasitic load and ejector's motive steam consumptions. Since 2017 many GPPs in Indonesia have no longer operated at constant full capacity following demand fluctuation, as stated in grid dispatcher's Daily Operating Plan. This condition brings up energy efficiency opportunity to reduce steam and electricity own use through modification or installation of the load-following controller in the ejector system and cooling water pumps. The study aimed to identify the best alternative in devising this adaptive feature in gas removal and circulating water systems from economic and technical aspects. Evaluation's methodology included the development of GPP process modeling and data validation, setting up an alternative framework, testing of GPP performance for each alternative with the calibrated model, and decision analysis from economic and technical aspects to select the best option. The evaluation showed that the ejector's motive steam flow controller was able to reduce auxiliary steam usage at maximum by 7% (equal to 0.7 MWe). In comparison, the circulation water flow controller with Variable Frequency Drive (VFD) could reduce pumps electricity use by 35% (0.76 MWe). The study results recommended the implementation of a motive steam flow controller over the pump's VFD, considering its economic performance, operation flexibility, and lower execution risk. A B S T R A KOperasi Pembangkit Listrik Tenaga Panas Bumi (PLTP) yang efisien dapat dicapai melalui penggunaan uap yang optimal pada turbin dan sistem pendukung (ejektor), serta pengaturan tekanan kondensor yang rendah untuk mencapai konversi energi maksimum di turbin. Pada hampir semua PLTP, kevakuman kondensor dijaga melalui sirkulasi air pendingin yang memadai, dan efektivitas operasi ejektor dalam menghisap akumulasi Non-Condensable Gas (NCG), yaitu CO2, dan H2S, serta dispersinya ke atmosfer. Pada umumnya PLTP didesain untuk beroperasi pada basis bebannya (100% kapasitas) sehingga kinerja peralatan penunjang seperti ejektor dan pompa tidak sensitif terhadap fluktuasi beban pembangkitan maupun perubahan kandungan NCG dari sumur. Hal ini mengakibatkan pemakaian listrik sendiri dan konsumsi uap ejektor pada PLTP cenderung tetap. Sejak 2017 banyak PLTP di Indonesia tidak lagi beroperasi dengan kapasitas penuh karena mengikuti fluktuasi permintaan grid seperti yang dinyatakan dalam Rencana Operasi Harian dari pengatur beban. Kondisi ini memberi peluang upaya efisiensi energi untuk mengurangi konsumsi listrik dan uap melalui modifikasi dan instalasi pengontrol load-following pada sistem kerja ejektor dan pompa sirkulasi air pendingin. Studi ini bertujuan untuk mengidentifikasi alternatif terbaik dalam merancang fitur adaptif ini, baik dari aspek ekonomi maupun teknis. Metodologi evaluasi mencakup pengembangan pemodelan proses PLTP dan validasi datanya, menyiapkan kerangka evaluasi alternatif, pengujian kinerja PLTP untuk setiap alternatif dengan model yang terkalibrasi, dan analisis pemilihan opsi terbaik secara ekonomi dan teknis. Hasil evaluasi menunjukkan bahwa pengontrol aliran uap motif pada ejektor mampu mengurangi penggunaan uap maksimum sebesar 7% (setara 0,7 MWe), sedangkan pengontrol aliran air sirkulasi dengan Variable Frequency Drive (VFD) dapat mengurangi penggunaan pompa listrik sebesar 35% (0,76 MWe). Hasil studi merekomendasikan penerapan sistem pengontrol aliran uap motif pada ejektor dibandingkan aplikasi VFD pada pompa dengan mempertimbangkan kinerja ekonomi, fleksibilitas operasi, dan risiko eksekusinya yang lebih rendah.